Are Private Markets and Filtering a Viable Source of Low-Income Housing? Estimates from a “Repeat Income” Model - Rosenthal, Stuart S. (American Economic Review, 2014)
While filtering has long been considered the primary mechanism by which markets supply low-income housing, direct estimates of that process have been absent. This has contributed to doubts about the viability of markets and to misplaced policy. I fill this gap by estimating a “repeat income” model using 1985–2011 panel data. Real annual filtering rates are faster for rental housing (2.5 percent) than owner-occupied (0.5 percent), vary inversely with the income elasticity of demand and house price inflation, and are sensitive to tenure transitions as homes age. For most locations, filtering is robust which lends support for housing voucher programs. (JEL R21, R31, R38)